Studies on the epidemiology of ringworm in cattle: Saadi A.G.AL-Samarrae ,Ouroba M.S.Ibrahim , And Jenan M.K.Najim - AL-Samarrae, Saadi A.G. (The Iraqi Journal of Veterinary Medicine, 2009)
The epidemiology of ringworm in two cattle herds in Baghdad area was studied during the period fromSeptember 2001 to August 2002.Two hundred skin scraping were collected from the infected area. Theprevalence of infection was 68%. In males it was lower (37.5%) than females (62.5%) and higher in less thanone year old animals. The prevalence was highest in January (16.5%). Eleven species of fungi were diagnosed,these include; Trichophyton verrucosum, T. rubrum,T.metagrophytes, Aspergillus fumigatus , A. flavus , A.Niger , A.terru , Mucor spp. , Altenaria alternata , Rhizopus and Fusarium spp. , one species of yeast Candidaalbicans.